In Vitro Efficacy Of Different Phytoextracts Against Alternaria Solani (Journal of Plant Disease Sciences, 2021)
Alternaria solani causes early blight disease in tomatoes, which is one of the most widespread and destructive diseases in major tomato-growing areas. To avoid relying solely on chemicals and to identify a viable alternative component, six phyto- extracts were tested in the lab against A. solani mycelial development. Over the untraded control, all six phyto-extracts tested against Alternaria solani showed considerable suppression of mycelial growth, which was found to increase with botanical with concentration of the botanicals tested. In plant extract, garlic clove extract was found effective inhibiting mycelial growth 71.23% followed by neem (64.06%), datura (53.10%) and Tulsi (43.10) while, aloevera was found least effective with least mycelium inhibition (38.18%).
Keywords: Alternaria solani; Early blight; Phyto-extracts; tomato and Mycelial inhibition